Frequency of Vitamin D Deficiency in Primigravida (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Adequate vitamin D levels during pregnancy are necessary to ensure adequate maternal responses to the neonatal handling and fetal demand of calcium. Deficiency of Vitamin D in pregnancy equally affect the women as well as their newborn, inturns can leads to high bone turnover, osteomalacia and vitamin Drelated myopathy in the mother. This study was planned to calculate vitamin D deficiency in primigravidasto create the awareness in general population, and obstetricians may take attention towards this important issue. Objective: The objective of this study was to calculate the frequency of lower vitamin D levels in primigravidas presenting at tertiary care hospital. Study Design: Descriptive cross sectional survey Study Duration: One year From 1st January 2015 to 31st December 2015. Place of Study: Sir Ganga Ram Hospital, Lahore Department of Obstetrics and Gynaecololgy Material & Methods: A total of 80 primigravida with singleton viable pregnancy between 20-35 years were included from OPD Sir Ganga Ram Hospital, Lahore, department of Obstetrics & Gynaecology, who were already diagnosed cases of deficiency of vitamin D and were taking vitamin D therapy were excluded, a written informed consent from the participants was obtained to include their data in the study. Maternal blood sample in a sterilized disposable syringe was collected in lab for measurement of 25 hydroxy vitamin-D levels by Elecsys method on Roche cobas e 411, and laboratory reports were reviewed by the researcher herself, deficiency of vitamin D was labeled as
Keywords: Pregnantwomen, primigravida, vitamin D deficiency